Camel mastitis in Southern Algeria - Saidi, Radhwane; Mimoune, Nora; Benaissa, Mohamed Hocine; Baazizi, Ratiba; Aissaoui, Fatma Zohra; Behalil, Messaouda; Khelef, Djamel; Kaidi, Rachid (2021)
In Algeria, camel breeding participates in the national milk production. However, this breeding faces significant health problems, including mammary pathologies. This disease is a major public health threat, due to the existence of human pathogens in milk. Several species are associated with this mastitis. Unlike cow"s milk, goat and camel milk are most often consumed in the fresh raw state, thus escaping any official control. The present study aimed to determine the nature and frequency of mastitis, and the nature and frequency of the responsible bacteria in each type of mastitis in southern Algeria. A total of 62 camels were subjected to clinical examination and screening for subclinical mastitis and the presence of Brucella using the California Mastitis Test (CMT) and ring test, respectively. CMT positive samples were then further subjected to bacteriological analysis. Clinical and subclinical mastitis were present with frequencies of 4.44% and 95.55%, respectively. Bacteriological analysis isolated a total of 73 samples of 45 seeds. Staphylococci were most commonly isolated, with a frequency of 63.01%. Among these, Staphylococcus aureus were at the top of the list, with 35.61%, while Staphylococcus SCN (coagulase negative staphylococci) represented only 27.39%. Streptococci were the second most isolated group, with 28.77%. Gram-positive bacilli were in third place, accounting for 6.85% of all isolates. Gram- negative bacilli (enterobacteria) were isolated with a frequency of 1.36%. Brucella was present with a frequency of 4.44%. Finally, an extended study on a larger sample of camels is required in the future.
U Alžiru, uzgoj deva sudjeluje u nacionalnoj proizvodnji mlijeka. Međutim, taj uzgoj suočava se sa zdravstvenim problemima, uključujući patologiju mliječnih žlijezda koja zauzima znatno mjesto. Ova bolest predstavlja glavnu prijetnju javnom zdravlju uslijed prisutnosti patogena opasnih za ljude u mlijeku. Naime, nekoliko bakterija povezano je s mastitisom. Za razliku od kravljeg mlijeka, kozje mlijeko i mlijeko deva često konzumiraju sami uzgajivači svježe i sirovo, čime se izbjegava službena kontrola. Ova studija imala je za cilj ustvrditi svojstva i učestalost mastitisa, kao i svojstva i učestalost opasnih bakterija u svakoj vrsti mastitisa u južnoj regiji Alžira. Ukupno 62 deve podvrgnute su kliničkom pregledu vimaa i prisutnosti brucele uporabom kalifornijskog testa za mastitis (CMT), odnosno ring testa. Pozitivni uzorci CMT testa podvrgnuti su bakteriološkoj analizi. Klinički i supklinički mastitis bili su prisutni s učestalošću od 4,44 %, odnosno 95,55 %. Bakteriološka analiza omogućila je izolaciju ukupno 73 uzorka 45 sojeva. Stafilokoki su najčešće izolirani s učestalošću od 63,01 %. Među njima, Staphylococcus aureus bio je najprisutniji s 35,61 %. Staphylococcus CNS (koagulaza negativni stafilokoki) predstavljali su 27,39 %. Streptokoki su bili druga najčešće izolirana skupina s 28,77 %. Gram-pozitivni bacili bili su na trećem mjestu sa 6,85 % izolata. Gram- negativni bacili (enterobakterije) izolirane su s učestalošću od 1,36 %. Brucela je bila prisutna s učestalošću od 4,44 %. Zaključno, u budućnosti će biti osmišljena proširena studija na većem broju deva.
Bibliografija: 20 jed.
Abstract ; Sažetak.
Keywords: Deve -- Devino mlijeko -- Mastitis -- Bakterije